Size Distribution of Ambient Particulate Matter and Its Constituent Chemical Species Involving Saccharides During Early Summer in a Chinese Megacity - Khan, Jahan Zeb; Sun, Long; Tian, Yingze; Dai, Qili; Hu, Tongxin; Feng, Yinchang (Frontiers in Environmental Science, 2021)
The ambient particulate matter (PM) pollution adversely influences the human health and natural environment. The size distribution is important for understanding the contributions and characteristics of ambient PM and its constituent chemical species. In present work, the size distribution and characteristics of the carbonaceous, ionic, elemental, and sugar species were categorically explored for the fraction-wise PM in Tianjin during 2018 early summer. The average concentrations were 32.4, 20.9, and 49.3 µg/m3 for the PM1, PM1-2.5, and PM2.5-10, respectively. The PM mostly distributed in the coarser PM2.5-10 (47%), moderately distributed in the finer PM1 (33%), and also considerably distributed in the intermodal PM1-2.5 (20%). The carbonaceous and ionic species exhibited bimodal distribution contributing mostly to the finer and then coarser fraction. The elemental species exhibited unimodal distribution contributing mostly to the coarser and then intermodal fraction. The specific sugar species indicated the biomass burning and primary biogenic contributions. The bimodal levoglucosan distribution indicated the significant biomass burning contributions to the finer and coarser fractions. The unimodal glucose, fructose, and arabitol distribution and the bimodal mannitol distribution indicated the dominant primary biogenic contributions to the coarser fraction, and there also considerable contributions to the finer and intermodal fractions. The PM1/PM10, PM1-2.5/PM10, PM2.5-10/PM10, OC/EC, SOC/OC, AE/CE, NO3-/SO42-, K+/EC, and levoglucosan/K+ ratios indicated the fraction-wise characteristics. The anthropogenic sources (combustion processes, traffic emissions, secondary particles, etc) contributed mostly to the finer PM1 and intermodal PM1-2.5 fractions, while the natural sources (primary biogenic, marine salt, mineral dust, etc) contributed mostly to the coarser PM2.5-10 fraction. This work is a significant addition to the multi-size ambient PM’s size distribution and characterization studies.